Formulation D’un Medicament Traditionnel Ameliore Anti Emetique A Base Des Graines De Garcinia kola Heckel - Ernest, Djoko; Yimta, Foutse; Rosine, Chougouo; Lydie Patricia, Simo Foko; Christelle, Wanga Nyamsi Richelmine; et Wouessidjewe Denis (International Journal of Current Innovations in Advanced Research, 2023)
Garcinia kola also called bitter kola is a fruit tree of Clusiaceae family. Its seeds are used in traditional medicine to treat many digestive, rheumatic and respiratory diseases. Unfortunately when they are dry, they become hard and unfit for consumption. In this study we wanted to develop an improved traditional medicine against nausea and vomiting, pathologies against which these seeds have the greatest report in the west region of Cameroon. To remain very close to traditional use we decided to prepare chewing pellets, with the aid of simple excipients (sucrose, lactose, cocoa butter). Those pellets contained 13.5% of Garcinia kola seeds powder corresponding to 0,1g of quercetin flavonoïds equivalents. The pellets were administered to a sample of 80 persons suffering from nausea or vomiting and they were very effective. On a dose of 4 pieces a day the effectiveness was 100%; all in all the patients were treated. The activity of the drug was obtained 10 minutes after its consummation. The pellets were active on nausea and vomiting that originates from motion sickness, helminthiasis and malaria. Finally, the preparation of chewing pellets can make Garcinia kola seeds favourable for consumption at anytime and anywhere; their effectiveness on nausea and vomiting is better than other drugs usually prescribed in case of those pathologies.